The Diagnosis and Treatment of Tuberculosis - Suárez, Isabelle; Fünger, Sarah Maria; Kröger, Stefan; Rademacher, Jessica; Fätkenheuer, Gerd; Rybniker, Jan (Deutsches Ärzteblatt international, 2019)
Around 10 million people worldwide contract tuberculosis every year. According to the World Health Organization (WHO), approximately one-quarter of the world's population is latently infected with Mycobacterium tuberculosis. In Ger- many, the incidence of tuberculosis was in decline over several decades but rose in 2015 to 7.3 new cases per 100 000 persons. In 2018, a total of 5429 new cases were documented, corresponding to 6.5 new cases per 100 000 persons.BACKGROUNDAround 10 million people worldwide contract tuberculosis every year. According to the World Health Organization (WHO), approximately one-quarter of the world's population is latently infected with Mycobacterium tuberculosis. In Ger- many, the incidence of tuberculosis was in decline over several decades but rose in 2015 to 7.3 new cases per 100 000 persons. In 2018, a total of 5429 new cases were documented, corresponding to 6.5 new cases per 100 000 persons.This article is based on literature retrieved by a selective search in PubMed and on the authors' clinical experience.METHODSThis article is based on literature retrieved by a selective search in PubMed and on the authors' clinical experience.Tuberculosis involves the lungs in almost 75% of patients but can generally involve any organ. In Germany, the majority of patients come from high-incidence countries. If a patient's differential diagnosis includes tuberculosis, the main tests for the detection of the pathogen in sputum and tissue samples are culture (the gold standard), microscopy, and nucleic acid amplification tests. Imaging studies are also used for diagnosis and follow-up. The standard treatment consists of a combination of isoniazid, rifampicin, ethambutol, and pyrazinamide, followed by a combination of isoniazid and rifampicin only. Liver damage is one of the more common adverse effects of this treatment, arising in 2.4% of patients. Multidrug-resistant tuberculosis, which is rare in Germany (around 100 cases per year), should be treated in special- ized centers.RESULTSTuberculosis involves the lungs in almost 75% of patients but can generally involve any organ. In Germany, the majority of patients come from high-incidence countries. If a patient's differential diagnosis includes tuberculosis, the main tests for the detection of the pathogen in sputum and tissue samples are culture (the gold standard), microscopy, and nucleic acid amplification tests. Imaging studies are also used for diagnosis and follow-up. The standard treatment consists of a combination of isoniazid, rifampicin, ethambutol, and pyrazinamide, followed by a combination of isoniazid and rifampicin only. Liver damage is one of the more common adverse effects of this treatment, arising in 2.4% of patients. Multidrug-resistant tuberculosis, which is rare in Germany (around 100 cases per year), should be treated in special- ized centers.Rapid diagnosis and targeted treatment are essential to prevent an unfavorable course of the disease as well as its transmission to other individuals. In patients presenting with unclear symptoms, tuberculosis should always be considered as a differential diagnosis. The diagnosis of latent tuberculosis and decision-making regarding its treatment are difficult because of the lack of specific biomarkers and of relevant data from clinical trials.CONCLUSIONRapid diagnosis and targeted treatment are essential to prevent an unfavorable course of the disease as well as its transmission to other individuals. In patients presenting with unclear symptoms, tuberculosis should always be considered as a differential diagnosis. The diagnosis of latent tuberculosis and decision-making regarding its treatment are difficult because of the lack of specific biomarkers and of relevant data from clinical trials.